THE STRATEGY OF COORPORATE CRIME COMPLIANCE IN THE BUSINESS PYRAMID THROUGH PENAL MEDIATION - Dewi Asri Yustia; Utari Dewi Fatimah; Leni Widi Mulyani (SAMPURASUN, 2019)
Abstract The form of corporate crime (business crime) in our research is the crime of investments with pyramid schemes, the initial concentration of the pyramid scheme is within the jurisdiction of civil law and economic law turns into a legal matter that enters the jurisdiction. This is because the company that develops the business does not have good faith in the management of the company (good governance) corporate crime settlement strategy in pyramid business which be done through penal mediation. Penal mediation may be made if the parties (offerors, offerees, and corporations) involved value each other and the results obtained in penal mediation, because the most important principle in penal mediation is the recognition of guilt and forgiveness by the injured party resulting from acts to achieve a win solution in the effort to bring responsibility for the perpetrator and the victim. In the criminal justice system at both level of investigation, prosecution and court proceedings there is a possibility of penal mediation by adhering to the principle of legal assurance, legal order and justice.